(untitled) (Revista LIDER, 2020)
The article has as its central purpose, to carry out an approach to the theoretical scope that exists in the plane of the concept of efficiency, with a clear approach to the university. In order to do so, the need to locate the definition of the concept of efficiency within the theoretical and doctrinal frameworks of those who, in different spheres, use such a name, starting from the comparison with the term of effectiveness, is considered.After the respective analysis of the previous question, we review approaches to the concept and its forms of measurement, to examine modalities of application in the study of specific processes in the university and more specifically academic. The approach, via case studies, show that, in general, it is possible to initiate such scrutinies in the eagerness of a new formula for the best description of the organizational and the processes that constitute it, sketching, additionally, a control device for its sustainability and development.